“Halewijn” in the shadow of the princess – “Chanson de geste” composition as art-based research in the light of integral interpretation - Daszkiewicz, Katarzyna; Załęcki, Jan (Melusine. Old Literature and Culture, 2025)
This article examines Jan Załęcki’s “Chanson de geste” composition inspired by the medieval Flemish ballad “Het lied van heer Halewijn”, whose adaptations formed the focus of his literary research. Applying the analytical methods of Mieczysław Tomaszewski, the study reveals the work’s complex and multifaceted vision of the Middle Ages, reinforcing its message as a universal legend of a valiant princess. The creative process was facilitated by the composer-literary scholar, who conducted a critical analysis of the portrayals of this heroine created by other authors. The case illustrates the value that creative activity can bring to scientific research, highlighting the effectiveness of arts-based research methodologies